Authoritarian diffusion or cooperation? Turkey's emerging engagement with China. Issue 7 (2nd October 2020) - Yilmaz, Gözde; Eliküçük Yıldırım, Nilgün
ABSTRACT: With the recent trend of autocratization in the world, scholars have begun to focus on authoritarian diffusion, cooperation, and autocracy promotion. Despite still being at an early stage theoretically and empirically, this expansion of diffusion literature has informed us about the possibilities of authoritarian diffusion and cooperation. In contrast to the recent focus on regional patterns of authoritarian diffusion and cooperation, this article explores a global process of authoritarian cooperation between Turkey and China. Focusing on the growing economic and political linkages between Turkey and China, we argue that, rather than authoritarian diffusion or autocracy promotion from China to Turkey, the increasing pragmatic cooperation among authoritarian states is the new game in town, shaped by interest-driven calculations to bolster power internally and internationally.